Dietary inflammation and cardiometabolic health in adolescents. Issue 2 (10th August 2020) - Sethna, Christine B.; Alanko, Daniel; Wirth, Michael D.; Shivappa, Nitin; Hebert, James R.; Khan, Samira; Sen, Sarbattama
Summary: Background: The Children's Dietary Inflammatory Index (C‐DII) has been validated to characterize the inflammatory potential of an individual child's diet. Objective: To determine the association between C‐DII and markers of cardiometabolic risk (adiposity, blood pressure [BP], lipids, albuminuria, glomerular hyperfiltration) in adolescents. Methods: Participants aged 12‐18 enrolled in NHANES from 2005 to 2014 who completed a 24‐hour dietary recall were included in this cross‐sectional study. Regression models adjusted for age, sex, race and height examined associations of C‐DII quartiles stratified by weight status. Results: Among adolescents (mean age 15 years), the average C‐DII score was 0.86 (SE 0.04). When comparing C‐DII quartile 4 (most pro‐inflammatory) to quartile 1 (most anti‐inflammatory), there was a positive association with albuminuria (OR 1.44, 95% CI 1.02, 2.03). After stratifying by weight status, C‐DII quartile was found to be significantly associated with albuminuria (OR 4.27, 95% CI 1.83, 9.92) and dyslipidemia (OR 1.87, 95% CI 1.15, 3.03) in adolescents who were overweight. Among adolescents with obesity, C‐DII quartile was associated with higher SBP ( β = 5.07, 95% CI 2.55‐7.59) and lower DBP ( β = −4.14, 95% CI −6.74, −1.54). Conclusion: Consuming a pro‐inflammatory diet in adolescence was associated with alterations in albuminuria, lipid and BP measures.